Cost savings from performance‐based maintenance contracting - Straub, Ad (International Journal of Strategic Property Management, 2009)
New procurement approaches combined with performance‐based building approaches should reduce costs, but empirical qualitative and quantitative studies are lacking. Performance‐based maintenance contracts give maintenance suppliers incentives to improve their way of working. Innovative, cost‐effective solutions that meet the performance criteria can be achieved, especially if the principle of whole‐life costing is being adopted. Indirect cost savings are expected as well. It enables maintenance contractors to assume responsibility for certain activities for which they are better equipped to perform than their clients. A calculation model was developed that calculates the net present value of the direct (product) and indirect (transaction) costs at project level for a competitive maintenance tendering approach and for performance‐based maintenance contracts. The findings show that performance‐based maintenance contracts reduce both direct and indirect costs compared to a competitive tendering approach. Essential preconditions are an early supplier involvement and longer term contracts, giving opportunities for maintenance product and maintenance process improvements.First Publish Online: 18 Oct 2010